Effect of extract concentration and ageing on optical Properties of biological silver nanoparticles (Funded Work) - PATIL SUNITA; MUTHUSAMY PALANISWAMY (International Journal of Pharma and Bio Sciences, 2017)
Biological synthesis of silver nanoparticles is an emerging trend in nanotechnology. The size, shape and optical properties of the silver nanoparticles can be controlled using plant extract concentration. A characteristic feature of noble metal nanoparticles is the strong color of their colloidal solutions, which is caused by the surface plasmon absorption. This size dependent electronic and optical property is possibly suitable for many electronic and photoelectronic applications. The UV-vis absorbance is used characterize the kinetics of formation, ï¬nal colloid stability and to study the structural and morphological features. This article describes the synthesis of silver nanoparticles using five different concentrations (2 ml to 10 ml) of Aegle marmelos fruit pulp extract to study the property of surface plasmon absorption during the process of synthesis and aging using UV-Visible spectroscopy. As extract concentration increases surface plasmon absorption and rate of synthesis increased with decrease in particle size by giving narrow absorption peak. During ageing silver nanoparticles synthesized from 8-10 ml extract concentration have shown slight change in peak position at higher wave length. The biological reducing agent and silver nitrate ratio can affect the rate of synthesis, surface plasmon properties and ageing process of biological silver nanoparticles.